Is V̇O2peak a valid estimation of V̇O2max in swimmers with physical impairments? - Feitosa, W.G. (2018)
Purpose: Peak and maximal oxygen uptake (V_O2peak and V_O2max, respectively) are used in assessing aerobic power. For swimmers with physical impairments, it is unclear whether the physiological variables obtained in 200-m and Nx200-m tests are similar. The objective of this study is to assess the validity of V_O2peak as an estimator of V_O2max and complementary physiological variables, in particular, carbon dioxide production (V_ CO2), respiratory exchange ratio (RER), minute-ventilation (V_ EÞ and absolute (HR) and relative (%HRmax) heart rates—which were obtained in a time trial test (200- m) and an incremental intermittent test (Nx200-m) performed by swimmers with physical impairments. Methods: Eleven well-trained swimmers with physical impairments performed 200-m all-out and Nx200-m from low to all-out (controlled by a visual pacer), both with a respiratory valve system and a portable gas analyzer. Results: A paired Student’s t-test showed no statistical difference (p > .05) for all comparisons. The intraclass correlation coefficient (ICC) was 0.97 and 0.98 for V_O2 in l/min and ml/kg/min, respectively; ICC = 0.75 to 0.9 for V_ CO2 (l/min and ml/kg/min), V_ E (in l/min) and HR (beats/min); ICC = 0.5 and 0.75 for %HRmax; and ICC < 0.5 for RER. Passing-Bablok regression showed that the dispersions were acceptable, considering the proportionality, except for HR and % HRmax. Bland-Altman method showed a high level of agreement for all variables. Conclusions: The _VO2peak and _VO2max, as well as the physiological variables _VCO2 and HR obtained, respectively, by 200-m and Nx200-m tests in swimmers with physical impairment were not different.